Determinação da configuração ótima de ciclo rankine orgânico para aproveitamento do calor rejeitado em usinas termelétricas com motores de combustão interna - Ribeiro, Letícia Costa (2017)
The Waste Heat Recovery (WHR) uses the heat that is normally discarded by a thermal system, and turns it into a useful form of energy. Among its benefits are: additional CO2-free energy, increased process efficiency and fuel economy. One of the alternatives to recover thermal waste is the application of Organic Rankine Cycles, in order to generate more power without increasing fuel consumption, which will lead to an increase in energy and environmental efficiency. In this work, the modeling and optimization is performed using the Engineering Equation Solver (EES) software to recoverytheheat from two thermal rejects, cooling water and exhaust gas, from the internal combustion engines (ICE) of a thermoelectric plant using Organic Rankine Cycles, with two configuration options, with and without regeneration. The optimization performed is thermoeconomic and parametric with the objective of minimizing the cost of the power generated, and selecting which workingfluid produces power at a lower cost. For this, thermodynamic and economical modeling are performed, forfive decision variables, among them the isentropic efficiencyof the pump and turbine. The main contribution of this work is to obtain and adjust cost equations capable of responding to these variables. The results showed that regenerative cycles for both heat sources, despite increasing cycle efficiency, produce a moreexpensive power than thecyclewithout regeneration. In the optimum condition,it is possible to obtain an increase of around 7% in the power generated by the thermoelectric plant.